Global characteristics of gravity waves in the upper atmosphere of Mars as measured by MAVEN/NGIMS - Siddle,AG; Mueller-Wodarg,ICF; Stone,SW; Yelle,RV (Icarus, 2019)
We present an analysis of gravity waves in Mars' upper atmosphere above 120km. Using in-situ data from NGIMS onboard MAVEN we have been able to characterise waves from nearly 4000 orbits. We have used temperature and density profiles to extract perturbations and interpret these as vertically propagating gravity waves which we characterise by their amplitude and wavelength. In this region of the atmosphere gravity waves have amplitudes of around 10%. Vertical wavelengths are found to be around 10–30km. We observe an increase in gravity wave amplitudes with increasing solar zenith angle. Gravity wave amplitudes appear invariant in altitude on the dayside, however increase with altitude on the nightside.